Determinants of Urban Waste Generation: A Case Study of Imopuro Subdistrict, Metro City - Farid Azfa Putra; Neli Aida; Vitriyani Tri Purwaningsih (International Journal of Economics, Business and Innovation Research, 2025)
The problem of food waste in urban areas is becoming an increasingly pressing issue due to increasing public consumption, population growth, and low awareness of waste management. This study aims to analyze the influence of various socio-economic factors on household food waste generation in Imopuro Subdistrict, Metro City. The method used is a quantitative approach with multiple linear regression techniques. The independent variables studied include years of education, number of family members, household expenditure on food, proportion of food expenditure, knowledge of waste management, and involvement in waste management. The results show that the number of family members, household expenditure on food, and proportion of food expenditure have a positive effect on food waste generation, while years of education, knowledge of waste management, and community involvement in waste management have a negative effect. These findings indicate the need for community education and empowerment in sustainable consumption practices as well as strengthening community-based policies for food waste management. This study is expected to serve as a reference for policymakers in designing effective and participatory waste management strategies.